PENGARUH WORK ETHICS TERHADAP KINERJA KARYAWAN DENGAN WORK LIFE BALANCE SEBAGAI VARIABEL INTERVENING PADA PT POS INDONESIA CABANG KEBONROJO SURABAYA - Alan, Nikolaus; Tandiyono, Tan Evan (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN (COMMUNITY OF RESEARCH LABORATORY), 2025)
PT. Pos Indonesia, which is one of the State-Owned Enterprises (SOEs) engaged in the service sector, is required to innovate in order to meet the demands of improving the quality of services to the community. The purpose of the research to be achieved is in accordance with the formulation of the problem that has been described above to know, analyze and answer the role of work ethics on employee performance with work life balance as an intervening variable at PT Pos Indonesia. The population in this study is employees of PT Pos Indonesia Kebonrojo Surabaya branch. For the population of employees of PT. Pos Indonesia Kebonrojo Surabaya branch totals 150 people. This study uses a quantitative approacher because the data used is in the form of a questionnaire, the respondents of this study are employees of PT. Pos Indonesia branch Kebonrojo Surabaya sample that will be taken as many as 60 employees. Based on the results of the study, it is known that the fourth hypothesis tested in this study, namely